Relationship between macrofauna, mineralogy and exchangeable calcium and magnesium in Cerrado Oxisols under pasture - Vendrame, Pedro Rodolfo Siqueira; Marchão, Robélio Leandro; Brito, Osmar Rodrigues; Guimarães, Maria de Fátima; Becquer, Thierry (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to assess the relationship between macrofauna, mineralogy and exchangeable calcium and magnesium in Cerrado Oxisols under pasture. Twelve collection points were chosen in the Distrito Federal and in Formosa municipality, Goiás state, Brazil, representing four soil groups with varied levels of calcium + magnesium and kaolinite/(kaolinite + gibbsite) ratios. Soil macrofauna was collected in triplicate at each collection point, and identified at the level of taxonomic groups. Macrofauna density showed correlation with contents of kaolinite, gibbsite and exchangeable Ca + Mg in the soils. Mineralogy and exchangeable Ca + Mg had significant effects on taxonomic groups and relative density of soil macrofauna. The termites (Isoptera) were more abundant in soils with low exchangeable Ca + Mg; earthworms (Oligochaeta), in soils with high levels of kaolinite; and Hemiptera and Coleoptera larvae were more abundant in gibbsitic soils with higher contents of total carbon.